The role and mechanisms of miRNA in neonatal necrotizing enterocolitis - Cai, Linghao; Lai, Dengming; Gao, Jiafang; Wu, Hao; Shi, Bo; Ji, Haosen; Tou, Jinfa (Frontiers in Pediatrics, 2022)
Neonatal necrotizing enterocolitis (NEC), the most significant causes of neonatal mortality, is a disease of acute intestinal inflammation. At present, it is not clear exactly how the disease is caused, but it has been suggested that this disorder is a result of a complex interaction among prematurity, enteral feeding and inappropriate pro-inflammation response and bacterial infection of intestine. A microRNA (miRNA) is a class of endogenous non-coding single-stranded RNA that is about 23 nucleotides long engaging in the regulation of the gene expression. Recently, numerous studies have determined that abnormal miRNA expression plays important roles in various diseases, including NEC. Here, we summary the role of miRNAs in NEC. We introduce the biosynthetic and function of miRNAs and then describe the possible mechanisms of miRNAs in the initiation and development of NEC, including their influence on the intestinal epithelial barrier’s function and on regulation of the inflammatory process. Finally, this review aids in comprehensive understanding of the current miRNA to accurately predict the diagnosis of NEC and provide ideas to find potential therapeutic targets of miRNA for NEC. In conclusion, our aims are to highlight the close relationship between miRNAs and NEC and to summarize the practical value of developing diagnostic biomarkers and potential therapeutic targets of NEC.